Resilience of Generation Z in Workplace - Laratmase, Antonia Junianty; Suhendar, Bagus; Ihsan, Muhamad; Andrean, Syahrial; Rahmani, Sofia F (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2025)
This study aimed to examine Generation Z’s level of resilience in facing challenges in the workplace. Generation Z is known to have unique characteristics as digital natives, but they are also susceptible to stress, anxiety, and burnout. Resilience is an important aspect in supporting their productivity and psychological well-being. This study used a quantitative approach with a descriptive survey method. Data were analyzed using descriptive statistics such as mean, median, mode, and standard deviation. The results showed that the average resilience score was above 3.5 for all indicators, with the majority of respondents showing a fairly good level of resilience. The mode and median were consistent at a score of 4 (agree), and the low standard deviation indicated a stable distribution of answers. These findings indicated that although Generation Z had good resilience potential, there was still room for strengthening, especially in the aspects of stress management and tolerance to discomfort.